2014
DOI: 10.1177/1534734614521236
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors of Diabetic Foot Ulcer With Multidrug-Resistant Organism Infection

Abstract: The objective was to determine multidrug-resistant organisms' (MDROs) profile in diabetic foot ulcers (DFU), antibiotic resistance of MDROs, and to find the potential risk factors for infection with MDROs. In 157 patients with DFU admitted to Tianjin Metabolic Disease Hospital, China, from January 2011 to January 2012, microbiological specimens were taken on admission. The patients were divided into 2 groups according to the infection of MDROs. Potential risk factors for MDRO-positive specimens were examined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 44 publications
5
39
5
1
Order By: Relevance
“…Ji et al . assessed wound grades, at categories of low and high scores encompassing the full spectrum of the severity of the diseases, and found no significant association between high scores on the Wagner classifications and an MDRO isolation, a finding analogous to our results showing the lack of an increase in risk of these types of infection where wounds are classified as high severity [ 13 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Ji et al . assessed wound grades, at categories of low and high scores encompassing the full spectrum of the severity of the diseases, and found no significant association between high scores on the Wagner classifications and an MDRO isolation, a finding analogous to our results showing the lack of an increase in risk of these types of infection where wounds are classified as high severity [ 13 ].…”
Section: Discussionsupporting
confidence: 87%
“…Previous publications suggest numerous demographic and clinical patient characteristics – including male gender, smoking history, HbA1c level, diabetes, previous treatment history and amputation – that seem to be strong predictors of the presence of P. aeruginosa [ 6 , 7 ]. Patients that require amputations are often those with the most severe infections and long standing, deep foot ulcers, characteristics of the wound previously linked to identification of P. aeruginosa [ 13 , 26 ]. This subpopulation of patients is also more likely to previously have received multiple courses of broad-spectrum antibiotics, which undoubtedly increases the risk of the emergence of MDROs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Contrary findings have however been documented from other studies in China, Iran and Portugal. 18,20,32 Our findings is also discordant with the report of Noor et al which established that ulcer size is a risk factor for infection by multidrug-resistant organisms. 31 This study also observed a significant association between presence of multidrug-resistant bacteria in IDFU and long duration of hospitalization (>1 months) similar to previously documented reports by another author in Turkey.…”
Section: Comparison Of Mean Values Was Done Using the Student's T supporting
confidence: 79%
“…In this study, 56% of the patients were hospitalised because of diabetic foot infection within the last three months, while antibiotic use within the last month was 52% and osteomyelitis occurred in 37% of the cases. The risk factors for MDR microorganism in DFI were reported to be prior antibiotic use and duration of antibiotics, prior hospitalisation or prior hospitalisation due to same wound, duration of hospitalisation, and presence of osteomyelitis (Ji et al, 2014;Hartemann-Heurtier et al, 2004;Richard et al, 2008;Kandemir et al, 2007).…”
Section: Discussionmentioning
confidence: 99%